2022
DOI: 10.1111/eve.13661
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin‐1 receptor influence in equine opioid sensitivity

Abstract: Summary Individual variation in opioid sensitivity can have a profound impact on the safety and efficacy of equine veterinary treatments, with the ability to adequately manage equine pain in a clinical setting currently limited. This review aims to explore the overlap between biological mechanisms associated with opioid metabolism and those mechanisms associated with coat colour in horses as has been documented in humans, with particular focus on the melanocortin‐1 receptor (MC1R) gene. In the future, the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 115 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…Notably, the dosage necessary for morphine's analgesic effect significantly surpasses that needed for its gastrointestinal side effects, approximately fifty-fold in humans and fourfold in experimental animals ( 46 , 47 ). In horses, morphine administered intravenously at dosages as low as 0.05 mg/kg, half the dosage typically used clinically to provide analgesia, decreased propulsive gastrointestinal motility for up to 6 h and significantly reduced defecation frequency, faecal matter weight and moisture content ( 9 , 39 , 48 – 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the dosage necessary for morphine's analgesic effect significantly surpasses that needed for its gastrointestinal side effects, approximately fifty-fold in humans and fourfold in experimental animals ( 46 , 47 ). In horses, morphine administered intravenously at dosages as low as 0.05 mg/kg, half the dosage typically used clinically to provide analgesia, decreased propulsive gastrointestinal motility for up to 6 h and significantly reduced defecation frequency, faecal matter weight and moisture content ( 9 , 39 , 48 – 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, morphine, a μ -opioid agonist, has been shown to decrease gastrointestinal propulsive motility and to increase PAC rates after orthopaedic surgery four-fold when administered intravenously at a dosage of 0.08–0.3 mg/kg compared to no opioid or butorphanol ( 5 , 9 , 35 , 39 , 40 ). Conversely, two other studies found no association between peri-anaesthetic intravenous morphine administration at a dosage of 0.1–0.17 mg/kg and increased PAC risk ( 6 , 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some studies developed in humans found a lower pain threshold in red-haired people. Genetic variations in the MC1R gene have been identified related to alterations in pain perception and sensitivity to analgesics [ 14 , 54 , 55 ]. Although the pharmacodynamics involved in analgesics are complex, coat color in the horse could play an important role as a possible phenotypic indicator of variations in sensitivity to opioids [ 55 ] and thus, in the response to stressors.…”
Section: Discussionmentioning
confidence: 99%